The Impact of Parental Presence on Their Children During Painful Medical Procedures: A Systematic Review. Issue 5 (28th August 2021) - Rheel, Emma; Malfliet, Anneleen; Van Ryckeghem, Dimitri M L; Pas, Roselien; Vervoort, Tine; Ickmans, Kelly
Abstract: Objective: Whether parental presence during their children's painful medical procedures is advantageous with regard to children's pain-related outcomes is questionable. Research on this topic is equivocal, and additional questions, such as whether levels of parental involvement may play a role as well, remain to be addressed. The purpose of this systematic review is to summarize and critically appraise the literature on the impact of parental presence vs absence during their children's painful medical procedures on the child's pain-related outcomes. Methods: The review protocol was registered on Prospero (ID CRD42018116614). A systematic search in PubMed, Web of Science, and PsycArticles resulted in 22 eligible studies incorporating 2, 157 participants. Studies were considered eligible if they included children (≤18 years old) undergoing a painful medical procedure and compared parental presence and/or involvement with parental absence during the procedure. Results: The children's pain-related outcomes included self-reported pain intensity, self-reported fear, anxiety and distress, observed pain-related behavior, and physiological parameters. Overall, evidence points in the direction of beneficial effects of parental presence vs absence with regard to children's self-reported pain intensity and physiological parameters, whereas mixed findings were recorded for children's self-reported fears, anxiety and distress, and observed pain-related behaviors. Conclusions: To provide clear recommendations on how to involve the parent during the procedure, as well as for which type of children and parents parental presence has the best effects, further research is needed, as indicated in this review.